Do animals have religion? Interdisciplinary perspectives on religion and embodiment - Schaefer, D (Taylor and Francis, 2012)
The field of religious studies has recently begun to explore a number of aspects of the relationship between animals and religion. The bulk of these explorations have been focused on reconsidering human ethical relationships with animals in light of religious values or exploring the textual and ritual meanings of animal bodies against the background of human religions. Another line of inquiry, the topic of this paper, looks at the religious experiences of animals themselves, and draws these questions into methodological conversations within the study of religion generally. This paper surveys a variety of approaches to animal religion from two disciplinary perspectives: comparative religion and cognitive ethology. From comparative religion, building on the work of Kimberley Patton, Jewish, Hindu, Buddhist, Creek, Cherokee, Christian, and Islamic understandings of the religious lives of animals are explored in turn. From cognitive ethology, two approaches are developed: a cross-species look at animal responses to death, building on the work of Marc Bekoff, and a specific look at religious practices within the order Primates. Ultimately, the paper concludes, the study of animal religion must proceed by thinking along two lines of recurring themes found throughout these accounts: the differences between animal bodies (what Jacques Derrida calls the “heterogeneous multiplicity” of animals) and the orientation of religious bodies to affect. Rather than thinking of religion as one thing, we must conceive of religion as multiple, corresponding to the multiplicity of embodied lifeways found among animals. And rather than thinking of religion as inextricable from belief, we must begin to explore the emotional patterns that make up religion among animals—human and nonhuman. These thematic anchors of animal religion have direct implications for the study of religion itself, especially in light of what Manuel Vásquez has called the “materialist shift” in religious studies.